Nineteenth Century Corporate Welfare: Municipal Aid and Industrial Development in Saint-Jean, Quebec, 1848-1914 - Lord, Kathleen (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
In the latter part of the nineteenth and early twentieth centuries, municipalities throughout Quebec used various means to attract railways and industries to their locality. Saint-Jean was no exception. The incentives its municipal leaders employed included investments, tax exemptions, loans, bonuses, land grants and other concessions. As was often the case in other towns and cities, the stimuli Saint-Jean offered had little favourable effect on the local economy, particularly the industrial sector.This paper attempts to discern the motives of the local entrepreneurial elite responsible for these actions. Insofar as this study has determined, economic weakness and competition from other more prosperous Quebec towns were at the root of the behaviour of Saint-Jean's leaders. Once a thriving centre for Canadian-American trade, Saint-Jean eventually suffered a decline in commercial activity in the 1870s as a result of the construction of the Grand Trunk Railway in the 1850s. The town's business elite thus tried to "boost" the industrial sector of the economy by generously dispensing municipal assistance. However, precisely because of the town's disadvantaged position, their efforts were largely futile.